Implementasi Perlindungan Upah Terhadap Sengketa Wanprestasi Pekerja Bangunan di Indonesia - Pradya Muharam Andika; Putu Ayu Veguita Putri Ningsih; Muhammad Arvin Wicaksono (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Problems with workers/laborers still often occur in various sectors in Indonesia, from all existing sectors, the construction sector is one of the largest absorbers of labor which is a concern for workers/laborers whether their rights and obligations have been implemented and fulfilled. Of the many problems in the construction sector, there is a problem that can be said to be at the core of life rather than the workers themselves, namely wages. Why wages have become a problem that is certainly a thing of the past but is still happening today. Because wages are a right that must be obtained by a worker, especially construction workers, the economic wealth of a construction worker also depends on how great the graduates or skills are and the size of the project. Of the many cases that occurred, there were construction workers who really only relied on one project for the survival of the workers and their families. In this case there is legal protection regarding this matter and is seen from the civil aspect. From the basic agreement to the court mechanism for cases or disputes over these rights.